Biflagellate spermatozoon structure of the hermaphrodite fish Satanoperca jurupari (Heckel, 1840) (Teleostei, Cichlidae) from the Amazon River - MATOS, Edilson Rodrigues (2015)
The ultrastructural features of the sperm were studied in the hermaphroditic teleost Satanoperca jurupari HECKEL, 1840 from Amazon River. Spermatocytes, spermatids and sperm develop in the testicular cysts among the different oocyte stages. Different stages of early spermatocyte development, mainly the ones with synaptonemal complexes were often observed. The mature spermatozoa belong to the introsperm type, with a short head (~ 3 mm long and 1.3 mm wide) without acrosome, short midpiece (~ 1.2 mm long and 1.8 mm wide) containing several mitochondria surrounding two centrioles and forming a mitochondrial collar. They have two flagella (each ~15 mm long) each of which has a common 9 + 2 microtubular pattern. Each flagellum has two opposite lateral cytoplasmic extensions that begin about 3 mm the midpiece still close to the end piece of flagellum.